Congenital hypothyroidism screening program in Turkey: a local evaluation - Kuşdal, Yusuf; Yeşiltepe-Mutlu, Gül; Özsu, Elif; Çizmecioğlu, Filiz Mine; Hatun, Şükrü (The Turkish Journal of Pediatrics, 2012)
It was aimed to evaluate the national congenital hypothyroidism program in terms of thyroid-stimulating hormone (TSH) cut-off level, frequency of cases that required treatment and the stages before treatment in the Kocaeli district area. This research was performed with the contribution of Kocaeli University Medical Faculty, Pediatric Endocrinology Department, and the Kocaeli Local Health District. 25,188 babies born in 2009 were evaluated. The previous laboratory data including heel prick samples and venous thyroid function tests (TSH, free/total T4 levels) of babies requiring investigation were evaluated retrospectively. 49,785 heel prick blood samples were collected from 25,188 babies born in our region. TSH levels of 3,355 babies in the first sampling were greater than the cut-off level (15 mIU/L) (recall rate was 13.3%). Venous sampling was required for 107 babies, and 39 of them needed to be treated (treatment rate was 1/645). Eleven of the babies who were treated were diagnosed with thyroid dysgenesis. Families of the babies who needed further venous sampling were given final results in an average of 28.5 days after the first heel sampling. We concluded that the recall rate is high, but raising the cut-off level for TSH may lead to overlooking the diagnosis of thyroid dysgenesis. The duration for providing final results to the families is quite long. It is necessary to take venous blood samples in the pediatric endocrinology units to reduce this duration.